2010
DOI: 10.1002/ajp.20852
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient transport within and between habitats through seed dispersal processes by woolly monkeys in north‐western Amazonia

Abstract: The contribution of vertebrate animals to nutrient cycling has proven to be important in various ecosystems. However, the role of large bodied primates in nutrient transport in neotropical forests is not well documented. Here, we assess the role of a population of woolly monkeys (Lagothrix lagothricha lugens) as vectors of nutrient movement through seed dispersal. We estimated total seed biomass transported by the population within and between two habitats (terra firme and flooded forests) at Tinigua Park, Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…We do not calculate changes to fertility from lateral diffusivity declines because accurate global maps of nutrient hotspots necessary for such a calculation do not exist at the necessary resolution. Previous experimental studies, however, have found that animals move significant quantities of nutrients across concentration gradients despite not necessarily moving dung from fertile to nonfertile areas (11,14,19). Regional models found that the transfer of P away from the Amazonian floodplains may have dropped by more than 50% following the extinction of the Amazonian megafauna (20,21).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We do not calculate changes to fertility from lateral diffusivity declines because accurate global maps of nutrient hotspots necessary for such a calculation do not exist at the necessary resolution. Previous experimental studies, however, have found that animals move significant quantities of nutrients across concentration gradients despite not necessarily moving dung from fertile to nonfertile areas (11,14,19). Regional models found that the transfer of P away from the Amazonian floodplains may have dropped by more than 50% following the extinction of the Amazonian megafauna (20,21).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, woolly monkeys (Lagothrix lagotricha) in Amazonia transported more P than arrives from dust inputs across a floodplain concentration gradient, without preferentially defecating in the less fertile area, merely by eating and defecating back and forth across the nutrient concentration gradient (19). If a small single species can transport such significant quantities of P, what is the role of all animals in an ecosystem over long periods of time?…”
Section: Significancementioning
confidence: 99%
“…In other words, animal movement generates a net transport of P from relatively nutrient-rich to relatively nutrient-poor areas, analogous to a diffusion process, but acting against the gradients of physical flow processes driven by topographic relief. For example, in a study of a woolly monkey (Lagothrix lagotricha lugens) population in northwest- ern Amazon, Stevenson and Guzmán-Caro (2010) showed that this population could import about 1-4 g P ha −1 a −1 from lowland to uplands through seed dispersal. A model based on animal movement as an agent of P redistribution illustrated how megafauna before the Pleistocene extinction could have sustained P cycling in this basin .…”
Section: P Redistribution Between Riverine and Terrestrial Ecosystemsmentioning
confidence: 99%
“…In addition, vertebrates can also play a role in nutrient cycling in tropical forests. In the Neotropics, primates increase the availability of accessible forms of nitrogen to plants, increase the speed of nutrient cycling (Feeley and Terborgh 2005), and move nitrogen from the fertile floodplain forests to upland forests that tend to be poor in nutrients (Stevenson and Guzmán-Caro 2010). Although these effects have been documented, the effects of defaunation on nutrient cycling remain poorly understood.…”
Section: Ecosystem Functionmentioning
confidence: 99%